A Study On The Implementation Of Water Resources Conservation Technology And Domestic Wastewater Management In the Building Design Of Dr. Heinz Frick House In Semarang And Turi House In Solo - Wuri Hamumpuni; Johanita Anggia Rini (Departement of Architecture, Universitas Islam Indonesia, 2017)
The objective of this study is to identify water conservation technology and domestic wastewater management in relation to building design. Water sanitation and conservation aspects were examined based on three parameters such as table checklist of Water as an Ecological Factor for a Sustainable Campus Landscape Journal of Procedia Social and Behavioral Science, method of DCBA Sustainable Housing in Indonesia and Greenship from Green Building Council Indonesia. Every parameter has benchmark that every building should attempt to fulfil as much as possible. This research used literature study, field survey, and interview with some relevant resource person to get relevant data based on related theories. The findings of the research found the values that indicate how far the implementation of water conservation technology and waste management in both research objects. Qualitative analysis is used to complete the three parameters of analysis and the quantity of water saving is also considered. Keywords: building, water contamination, water conservation, waste water management, building design.